Organising pneumonia as the first manifestation of rheumatoid arthritis. (24th March 2011) - Hoshino, Chisho; Satoh, Noriyuki; Narita, Masashi; Kikuchi, Akio; Inoue, Minoru
Abstract : Organising pneumonia (OP) is an inflammatory lung disease with distinctive clinicopathological features. OP can be evident during the course of rheumatoid arthritis (RA) with increased disease activity. The authors report an OP associated with RA case in which pulmonary symptoms preceded the onset of joint symptoms. An OP patient with elevated serum anticyclic citrullinated peptide antibody is likely to manifest RA in the near future, reflecting its high disease activity. Thus, an early rheumatologic consultation should be taken into consideration to make an early decision to initiate disease-modifying antirheumatic drugs therapy.